PORÓWNANIE WYNIKÓW ZASTOSOWANIA ALGORYTMÓW GENERALIZACJI KARTOGRAFICZNEJ DO UPROSZCZENIA LINII BRZEGOWEJ WYBRANYCH WÓD POWIERZCHN IOWYCH Z BAZY BDOT10K - Cybulski, Paweł (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The article discusses the issue of cartographic generalization of surface waters based on algorithms. In the process of developing topographic maps, spatial databases play an important role, in particular, BDOT10k. According to the regulation which regulates how to make topographic maps, there are no defined principles for generalization. Therefore, the article analyzes the simplification results of three algorithms and compares them with respect to their suitability for cartographic generalization of the chosen surface waters.